Regularity Criteria to the Axially Symmetric Tropical Climate Model Without Swirl (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider the Cauchy problem of the axially symmetric tropical climate model with fractional dissipation. By using the energymethod, we establish a new regularity criteria for the axisymmetric solutionsof the 3D Tropical climate model without swirl.